Synthesis and characterization of Li2ZnTi3O8 spinel using the modified polymeric precursor method - Camara, MSC; Lisboa Filho, Paulo Noronha [UNESP]; Cabrelon, M. D.; Gama, L.; Ortiz, W. A.; Paiva-Santos, C. O.; Leite, E. R.; Longo, Elson [UNESP] (Elsevier B.V., 2003)
In this work we report the synthesis procedure, crystallographic, structural and magnetic properties of the Li2ZnTi3O8 spinel obtained using a modified polymeric precursor method. This synthesis method generates very reactive and property-controlled nanoparticles. The samples were characterized using X-ray powder diffraction (XRD) associated to the Rietveld refinement method, thermogravimetric analysis (TG), specific surface area, scanning electron microscopy (SEM) and magnetic susceptibility measurements.The phase formation temperature of the lithium zinc titanate spinel was observed to decrease due to the homogeneity and highly controlled nanometric particle size. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: ceramic; electronic materials; chemical synthesis; crystal structure